Power of emperor in Russian legal discourse of second half of 19th– early 20th centuries: justification and options for interpretation - I. G. Adoneva; Yu. V. Druzhinina (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to resolving the issue of how the legal intellectual elite of the period under review understood the imperial power, its origin, capabilities and authorities. The legal professorship formed an outwardly consistent discourse between the theoretical aspects of state law and the content of the Basic State Laws of the Russian Empire: teachers had to justify and explain the existence of the unlimited power of the monarch. They analyzed the courses of state law developed by nine professors of the Imperial Universities and the School of Law. The methodological basis of this study is the history of intellectual culture as an analysis of legal ideas and discourses in the context of the second half of the 19th - early 20th centuries. The power of the emperor is characterized by the authors of textbooks in a section that is most often called «On the Supreme Power». Russian autocracy was described by jurists in a conceptual and categorical apparatus borrowed from their European colleagues. Legal scholars were looking for a balance between their own personal and scientific ideas and the form of government that existed in the Russian Empire. Despite the differences in the political outlook, they saw the reason for the Russian autocracy in the historical development: a vast territory, low population density, and the virtual absence of a struggle between the government and society. For state scholars closely associated with Western jurisprudence, who shared its values, it was important to emphasize the belonging of the Russian Empire to the European world, where a skeptical view of the Russian monarchy remained. This way out was the idea of legality. Without disputing the content of the «Fundamental State Laws» and guided by censorship considerations, the professors tried to convey to the student university audience the idea that the bureaucratic apparatus formed in the empire is a natural limiter of the imperial power; the legal framework is an obstacle to despotism, and the judiciary is in fact independent. This kind of theoretical constructs became a compromise between the preservation of absolute monarchical power and the worldview of those jurists who shared liberal values